(untitled) (Vietnam Journal of Community Medicine, 2025)
DEHEMA is an herbal product developed from an ancient remedy prescribed for pain, swelling, and bruises caused by injury. Objectives: Evaluate the anti-swelling, anti-bruises effects of DEHEMA in soft tissue injuries model. Method: Rabbits were subjected to soft tissue trauma to the ears and administered with two doses of DEHEMA (6 ml/kg/day or 12 ml/kg/day) or Celecoxib 24 mg/kg/day for 10 consecutive days. The lesions on the rabbit ears were observed, and the thickness of the rabbit ears and the area of ​​the lesions were measured. Results: DEHEMA at both doses faster recovery damage, reduced bruising and congestion compared to the model group; reduced the thickness and area of ​​the damaged area in rabbits compared to the model group with statistical significance at the time points after 3-7 days (p < 0.05) and was not different from the group taking Celecoxib (p > 0.05). Conclusion: DEHEMA were effective in reducing swelling and bruises in the soft tissue injury model.